Structural and microstructural behaviour of SnO2 dense ceramics doped with ZnO and WO3 - Perazolli, L.; Simoes, A. Z.; Coleto, U.; Moura, F.; Gutierrez, S.; Santos, COP; Carrio, JAG; Marques, RFC; Varela, José Arana [UNESP] (Elsevier B.V., 2005)
SnO2-based varistors doped with ZnO and WO3 were prepared by mixed oxide method. Experimental evidence shows that the increase in ZnO amount increases the volume and microstrain of unit cell while the WO3 promotes a decrease. The effect of ZnO and WO3 additives could be explained by the substitution of Sn4+ by Zn2+ and W6+. The addition of WO3 inhibits the grain growth due to the segregation in the grain boundary without influence in the densification of the samples. Besides that, an increase in the electrical resistance of the SnO2-ZnO-WO3 system was observed independent of the WO3 concentration. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: varistor; tin dioxide; rietveld analyses